The Influence of Firm Size, Audit Firm Size and Audit Opinion Towards Audit Delay - Wynne Nurul Faizah; Friska Ferisha; Cynthia Belinda; Carmel Meiden (Prodi Akuntansi FEB UNITOMO, 2022)
This study aims to determine whether the effect of firm size, KAP size and KAP size on audit delay. This study uses quantitative data analysis techniques with meta-analysis methods. The data of this study were obtained from observations of student thesis and journals at several universities related to the topic of audit delay. The results of this study indicate that the size of the company has a significant effect on audit delays, the size of the public accounting firm shows an influence on audit delays, and audit opinion has a significant effect on audit delays. So it can be said that the results of integrating several studies with meta-analysis show that there is an effect of size, size of KAP and audit opinion that is invested during the audit.